Product Branding Nata De Legen Dusun Shoberoh Desa Dalegan Kecamatan Panceng Kabupaten Gresik - I’lamatul Laili (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2019)
This article discusses the process of product branding “Nata de Legen” conducted by the Legen Shoberoh Group (KLS) and the media used. This research uses a qualitative approach. The aim is to describe the product branding process and the media used by KLS in marketing Nata de Legen. The results showed that the product branding carried out by KLS includes four stages; recognition, attracting consumers, marketing, and customer loyalty. In product branding, KLS optimizes services and provides empathy to customers with personal communication. The media used in the product branding process are social media Facebook and Whatsapp, then the point of purchase, namely the Dalegan White Sand tour